Chinese Students Learning English as a Second Language - Maria McQuade; Dora Jue Pan; Jana Chi-San Ho; JingTong Ong; Melody Chi Ying Ng; Xiangzhi Meng; Catherine McBride (MDPI AG, 2024)
The way in which different cities teach children to read in Chinese may have an impact on the skills they later utilize to acquire English word reading skills. This study examined the relative contributions of several cognitive-linguistic measures to English word reading for Chinese students learning English as a second language in two Chinese cities, one whose school system teaches Pinyin (Beijing) and one whose school system does not teach Pinyin (Hong Kong). Students in grades 2-3 completed measures on Chinese morphological awareness (MA), Chinese phonological awareness (PA), Pinyin writing, and English word reading. In the Beijing group, it was found that PA (β = 0.334, p < 0.01) and Pinyin (β = 0.257, p < 0.05) were significant predictors of English word reading. In contrast, in the Hong Kong group, only MA (β = 0.263, p < 0.05) was found to be a significant predictor of English word reading. The difference in predictors could be due to the availability of a phonological tool (Pinyin) for the Beijing students when learning Chinese, while the Hong Kong group may have relied more heavily on learning using MA and rote memory techniques. Overall, the results from this study provide data supporting the benefits of having a phonological tool like Pinyin for Chinese children when learning to read in English.